Physicochemical properties, cytocompatibility and antibiofilm activity of a new calcium silicate sealer - Zordan-Bronzel, Cristiane Lopes [UNESP]; Tanomaru-Filho, Mario [UNESP]; Torres, Fernanda Ferrari Esteves [UNESP]; Chávez-Andrade, Gisselle Moraima [UNESP]; Rodrigues, Elisandra Marcia [UNESP]; Guerreiro-Tanomaru, Juliane Maria [UNESP] (FapUNIFESP (SciELO), 2021)
The aim of this study was to evaluate the physicochemical properties, cytocompatibility and antibiofilm activity of a new calcium silicate-based endodontic sealer, Sealer Plus BC (MK Life, Brazil), in comparison with TotalFill BC Sealer (FKG Dentaire SA, Switzerland) and AH Plus (Dentsply, Germany). Setting time and flow were evaluated based on ISO 6876 standard. The pH was evaluated after different periods, and radiopacity by radiographic analysis (mmAl). Solubility (% mass loss) and volumetric change (by micro-CT) were assessed after 30 days of immersion in distilled water. Cytocompatibility was assessed by methyltetrazolium (MTT) and neutral red (NR) assays, after exposure of Saos-2 cells to the sealer extract for 24 h. An additional analysis was performed by using MTT assay after 1, 3 and 7 days of exposure of Saos-2 to the sealers 1:8 dilution extracts. Antibiofilm activity against Enterococcus faecalis and/or Candida albicans was evaluated by crystal violet assay and modified direct contact test. The physicochemical properties were analyzed using ANOVA/Tukey tests; MTT and NR data were analyzed by ANOVA and Bonferroni tests; the antimicrobial tests were analyzed by Kruskal-Wallis and Dunn tests (α=0.05). Sealer Plus BC had proper setting time, radiopacity, flow and alkalization capacity. Sealer Plus BC was significantly more soluble than AH Plus (p<0.05) and presented volumetric change similar to AH Plus and TotalFill BC (p>0.05). Sealer Plus BC presented antibiofilm activity and no cytotoxic effect. In conclusion, although Sealer Plus BC had higher solubility, this sealer showed proper physicochemical properties, cytocompatibility, and antibiofilm activity.
Keywords: Biofilms; Calcium Silicate; Materials Testing; Physicochemical Analysis; Root Canal Obturation